2014
DOI: 10.1038/srep04292
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Catalytic Triad of Family S46 Exopeptidases, Closely Related to Clan PA Endopeptidases

Abstract: The exopeptidases of family S46 are exceptional, as the closest homologs of these enzymes are the endopeptidases of clan PA. The three-dimensional structure of S46 enzymes is unknown and only one of the catalytic residues, the serine, has been identified. The catalytic histidine and aspartate residues are not experimentally identified. Here we present phylogenetic and experimental data that identify all residues of the catalytic triad of S46 peptidase, dipeptidyl aminopeptidase BII (DAP BII) from Pseudoxanthom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 50 publications
4
23
0
Order By: Relevance
“…putrefaciens [20], P. mexicana [18], and Capnocytophaga canimorsus [29]. At present, though their homologues are widely distributed among eubacteria, most S46-family members are tentatively classified by their sequence similarity to authentic S46 members of P. gingivalis, and their enzymatic characteristics remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…putrefaciens [20], P. mexicana [18], and Capnocytophaga canimorsus [29]. At present, though their homologues are widely distributed among eubacteria, most S46-family members are tentatively classified by their sequence similarity to authentic S46 members of P. gingivalis, and their enzymatic characteristics remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the S46 family is composed of three members, DPP7 (S46.001), DPP11 (S46.002), characterized in P. gingivalis (PgDPP7, PgDPP11, respectively), and DAPBII from Pseudoxanthomonas mexicana (S46.003) [18,19]. Since the biochemical property and substrate preference of DAPBII are nearly identical to those of PgDPP7, the S46 family should be composed solely of two members, i.e., DPP7 preferentially liberates dipeptides with both P1 and P2 hydrophobic residues, and DPP11 is specific for P1 Asp and Glu.…”
Section: Introductionmentioning
confidence: 99%
“…DAP BII sequentially releases Asp-Arg, Val-Tyr, Ile-His, Pro-Phe, and His-Leu from the N terminus of angiotensin I to degrade it completely into dipeptides10. The S1 site of DAP BII has a tendency to prefer a large hydrophobic side chain11, although strict specificity is not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, we tried to solve the structure of PgDPP11 by molecular-replacement techniques. Structures of DAP BII complexed with or without a peptide (Sakamoto, Suzuki, Iizuka, Tateoka, Roppongi, Okada et al, 2014), belonging to the S46 peptidase family (Suzuki et al, 2014) and having 29% sequence identity with PgDPP11, were used as search models. Since these attempts failed, a search for heavyatom derivatives intended for phasing by the multiple/single isomorphous replacement method and the preparation of selenomethionine-substituted PgDPP11 using LeMaster medium (Hendrickson et al, 1990) and E. coli B834(DE3) cells for phasing by Se-MAD/SAD methods are under way.…”
Section: Figurementioning
confidence: 99%
“…The predicted amino-acid sequences of DPP7s and DPP11s from Porphyromonas species revealed that these enzymes are $80 kDa serine proteases and are classified into clan PA family S46 in the MEROPS database (Rawlings et al, 2012). The S46 enzymes are widely distributed in anaerobic Gram-negative species in the genera Bacteroides, Parabacteroides and Porphyromonas, but are not found in mammals (Ohara-Nemoto et al, 2011;Suzuki et al, 2014). In order to further characterize the properties of the S46 enzymes, we initiated structural studies of PgDPP11.…”
Section: Introductionmentioning
confidence: 99%